Procedural sedation associated displacement of sharp oesophageal foreign body. (20th March 2012) - Sondhi, Vishal; Patnaik, Suprabha Kumari; Khullar, Atul
Abstract : Oesophageal foreign body is a common clinical problem. The therapeutic intervention varies from endoscopic removal to observation for spontaneous passage of foreign body. The authors illustrate a case of sharp board pin ingestion by a child, which stayed impacted at C7 –T1 level for 8 h with indentation of tracheal mucosa. However, upon administration of midazolam and ketamine for procedural sedation, the pin spontaneously advanced to stomach when muscle relaxation had set in. A few oesophageal mucosal erosions were noted on the endoscopy. The foreign body could not be retrieved by the procedure and was spontaneously egested impacted in faeces. This case presents a distinctive hazard associated with procedural sedation for a foreign body in aero-digestive tract, where the associated muscle relaxation can lead to complications due to spontaneous movement of foreign body.